Understanding Inclusive Education in the “Front of the Class” Movie in Chinese Perspective - Tan, Qinyi; Liu, Wan; Teng, Luyan (Journal of Education, Health and Sport, 2022)
To explore the beliefs of Inclusive Education in the film " Front of the class ", this study uses the method of content analysis to interpret and analyze this film from the perspective of the concept of inclusive education, inclusive family, inclusive school, and inclusive society. It found that the film contains rich beliefs and concepts of inclusive education, which helps to pursue the quality of education examine educational equity and social equity, provide intellectual support for the construction of inclusive society, responding the UN's sustainable development goal 4 (SDG 4) focuses on ensuring inclusive and equitable, quality education and lifelong learning opportunities for all.